EFFECTS OF VACCINIUM MYRTILLUS L. EXTRACT ON TNF-α-INDUCED INFLAMMATION THROUGH HUMAN PARAOXONASES - Balbal B.; Bitmez B.; Albayrak I. G.; Gultekin S. K.; Akalin E.; Salihler K.; KARTAL M.; ATASEVER ARSLAN B. (My University, 2023)
Cardiovascular diseases (CVDs) is a leading cause of death worldwide, and is characterized by a range of conditions that affect the heart and blood vessels. The extract of Vaccinium myrtillus L. fruit has been found to have cardioprotective effect. Human paraoxonases ( PON1 , PON2 , PON3 ) genes play an important role in protecting against the development of CVDs by acting as antioxidants and anti-inflammatory agents. The present study aimed to investigate the chemical constituents and cardioprotective effects of V. myrtillus L. extract on TNF- alpha inflammation and oxidative stress in ECV-304 human endothelial cell line and the potential role of human paraoxonases in these effects. The results indicated that V. myrtillus L. extract has cardioprotective effects against inflammation and oxidative stress in ECV-304 cells, and these effects may be mediated through the upregulation of PON1 , PON2 , and PON3 genes. These findings suggest that V.myrtillus L. may have therapeutic potential for the prevention and treatment of CVDs.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences